Investigasi Determinan Faktor yang Memengaruhi Penyalahgunaan Aset pada Perguruan Tinggi - Ardi, Pahmi; Urumsah, Dekar (Owner : Riset dan Jurnal Akuntansi, 2024)
This study uses the fraud star theory approach to analyze the factors that influence asset missaproriation. The factors tested in this study are financial pressure, internal control system, quality of human resources, organizational culture, and integrity. The research uses a quantitative approach with a survey method of dsitributing questionnairies online. A total of 146 respondents related to asset management at univirsities in west kalimantan province became research respondents who were then tested and analyzed using Structural Equation Modelling (SEM) with the help of Smart PLS 3.3.3. The results showed that financial pressure and the quality human resources positively and signifianctly affected asset misuse. Organizational culture has a positive but insignificant effect on asset misuse. While the internal control system has a negative but insignificant effect on asset misuse, integrity has a negative and significant effect on asset misuse. The result of this study contribute as a reference for universities in implementing asset management policies wich can then be seen based on factors that influence asset misuse such as employees or official financial pressure, the quality human resources in the organization, the organizational culture that has been implemented in the organization, and integrity of employees. Good internal control system is also very important in universities an an effort so that asset management in universities can be carried out.